Civic Education Wawasan Kebangsaan di Kalangan Gen Z di Kota Palembang - Fathi, Al; Amaliatulwalidain, Amaliatulwalidain; Kariem, M Qur’anul (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2023)
This research was conducted to find out how the National Unity and Politics Agency of Palembang City is implementing citizenship education with a national perspective for generation Z in the future. Palembang city in 2022. This research uses a qualitative approach, namely using research methods with data collection techniques, namely observation, interviews and documentation. based on Civic Education theory which consists of 3 (three) indicators, namely: Civic Education Competency (Civic Knowledge), Civic Attitude Competency (Civic Dispositions), Civic Attitude Competency (Civic Skills). It can be concluded that the role of the Palembang City Kesbangpol Agency in citizenship education, especially for generation Z in Palembang City, is quite good with a target of 60 junior high schools and the planned programs are being implemented well. There are 2 inhibiting factors in the implementation of further education, such as skills education and special attitude education. The first inhibiting factor is the lack of human resources and the second inhibiting factor is the lack of funds to implement specific follow-up programs